2022
DOI: 10.15406/aovs.2022.12.00409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corneal cross linkage (CXL) on intraocular pressure (IOP) measurements in keratoconus patients

Abstract: This study aims to determine the effect of corneal cross-linkage (CXL) on intraocular pressure (IOP) in keratoconus patients. Methods: A quasi-experimental study was carried out at the Cornea Clinic of Al Ibrahim Eye Hospital Malir, Karachi. A total of 60 eyes of 36 subjects with progressive keratoconus with the age range of 15 to 31 years were fulfilling the criteria of the study. Subjects were selected with convenient sampling and subjects with a previous history of CXL were excluded from the study. A compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, Waheed et al reported a statistically significant decrease in GAT measured IOP on the same day after CXL ( P = 0.001), with no statistically significant change in IOP on the 2nd day, at 1 month and 3 months postoperatively. These results could be attributed to the fact that Waheed et al applied epithelium-on (epi-on) CXL technique, raising further concerns regarding the efficacy of epi-on CXL when compared to standard epi-off CXL [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Waheed et al reported a statistically significant decrease in GAT measured IOP on the same day after CXL ( P = 0.001), with no statistically significant change in IOP on the 2nd day, at 1 month and 3 months postoperatively. These results could be attributed to the fact that Waheed et al applied epithelium-on (epi-on) CXL technique, raising further concerns regarding the efficacy of epi-on CXL when compared to standard epi-off CXL [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%